Association between Iron, TIBC and Ferritin with Thyroid Hormones Levels in Patients Referred to Shouride Clinic Laboratory - Roya Sehat; Esmaeil Shahabi Satlsar; Parichehr Hanachi (Tehran University of Medical Sciences, 2019)
Background and Aim: Iron deficiency is one of the most common nutritional disorders in the world, and it may affect the metabolism and function of a number of proteins, including the level of thyroid hormones. As such, fluctuations in the level of thyroid hormones may also affect the bodychr('39')s iron status. The present study aimed to evaluate the relationship between thyroid hormones and the status of iron stores. Materials and Methods: The study populations included referral patients to laboratory of Shourideh clinic in Mashhad, Iran. Fe, Ferritin, TIBC (total iron-binding capacity), TSH, T4, T3, and CRP tests were performed with a physicianchr('39')s request. The target sample size was a total of 420 patients including 287 women and 133 men with an average age of 41.5 years. TSH and Ferritin test were measured by Elisa method, Fe and TIBC were measured by automated method. Results: The results showed no significant relationship between the bodychr('39')s iron status and thyroid hormones level (P˃0.05). Interestingly, in subjects with lower iron level, TSH was at the highest level and T4 was at the lowest level. However, no positive relationship was found between iron status and T3 level. Conclusion: Although, there was no significant relationship between iron status and thyroid hormones level in the present study, it seems that the fluctuations of each of them may affect somehow the other.